2021
DOI: 10.1002/biof.1706
|View full text |Cite
|
Sign up to set email alerts
|

Role of luteolin in overcoming Parkinson's disease

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder affecting elderly people (>60 years old) worldwide. There is no permanent cure for the disease but the symptomatic relief can be obtained by using dopamine agonists besides L-dopa therapy. The longer use of the drugs is associated with several side effects. Hence, the researchers have made a considerable attention toward the development of neuroprotective agents from plants. A number of phytochemicals have been demonstrated for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 64 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…shown that luteolin has protective effects on scopolamine-inducedamnesia, 44 Parkinson's, 45 and motor disorders 46 due to its effect on DA. Although the protective effect of luteolin on antipsychotics and antidepressants has been shown in various articles, 47,48 it has been shown that administrations of luteolin tend to decrease dopamine levels in animals with amnesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shown that luteolin has protective effects on scopolamine-inducedamnesia, 44 Parkinson's, 45 and motor disorders 46 due to its effect on DA. Although the protective effect of luteolin on antipsychotics and antidepressants has been shown in various articles, 47,48 it has been shown that administrations of luteolin tend to decrease dopamine levels in animals with amnesia.…”
Section: Discussionmentioning
confidence: 99%
“…One of the flavonoids found in most medicinal plants is luteolin, which has neurotrophic effects by promoting neuronal survival and neuritis outgrowth 43 . Previous studies have shown that luteolin has protective effects on scopolamine‐induced‐amnesia, 44 Parkinson's, 45 and motor disorders 46 due to its effect on DA. Although the protective effect of luteolin on antipsychotics and antidepressants has been shown in various articles, 47,48 it has been shown that administrations of luteolin tend to decrease dopamine levels in animals with amnesia 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the diverse health benefits of luteolin, its anti-cancer, anti-microbial, anti-inflammatory, antioxidant, and anti-diabetic effects have been studied in detail in various cell types and mouse models ( Muruganathan et al, 2022 ). Additionally, luteolin is blood-brain barrier permeable and is reported to have a neuroprotective effect in cell culture and animal models of Alzheimer’s ( Wang et al, 2016 ), Parkinson’s ( Siddique, 2021 ), and Huntington’s ( Oliveira et al, 2015 ) disease. A combination of luteolin and quercetin also proved effective in reducing symptoms of autism spectrum disorders (ASD) ( Taliou et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to multiple docking studies, luteolin prevents alpha‐synuclein from aggregation, thus hindering the formation of Lewy bodies, which may prevent the death of dopaminergic neurons. [ 13 ] Luteolin decreases oxidative stress, suppresses inflammation, microglia activation, neurotoxicity, acetylcholinesterase (AChE), and tau phosphorylation, prevents the production of β‐amyloid plaques, and blocks inflammation brought on by fibrillary β‐amyloid, prevents mast cell cytokine production and decreases zinc‐induced tau phosphorylation, hampers the formation of Aβ 42 plaque, minimizes mucin‐type O ‐glycosylation concerning amyloid precursor protein, and improves memory. Interestingly, quercetin (structural analog of luteolin) has shown potential in diminishing neuroinflammation, including the activity of microglia, and could offer benefits in the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%
“…According to multiple docking studies, luteolin prevents alpha-synuclein from aggregation, thus hindering the formation of Lewy bodies, which may prevent the death of dopaminergic neurons. [13] Luteolin decreases oxidative stress, suppresses inflammation, microglia activation, neurotoxicity, CCL2 and CCL5 from human mast cells. Remarkably, tetramethoxyluteolin has been proposed as a prospective treatment for neurodegenerative conditions.…”
mentioning
confidence: 99%